2004
DOI: 10.1186/1471-2474-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders : A survey of physical therapists in Izmir-Turkey

Abstract: Background: This study was planned to collect data about causes, prevalence and responses to work-related musculoskeletal disorders reported by physiotherapists employed in Izmir, Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
133
6
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 22 publications
31
133
6
14
Order By: Relevance
“…The lifetime prevalence of WRMD for physical therapists was reported as 55% 11) in Australia, 68% 12) in the United Kingdom, and 85% 1) in Turkey. Treatment areas that triggered WRMD most were musculoskeletal outpatient care (31%), followed by neurological rehabilitation (14%), and elderly care (12%) 12) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lifetime prevalence of WRMD for physical therapists was reported as 55% 11) in Australia, 68% 12) in the United Kingdom, and 85% 1) in Turkey. Treatment areas that triggered WRMD most were musculoskeletal outpatient care (31%), followed by neurological rehabilitation (14%), and elderly care (12%) 12) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most previous studies have reported that therapists experience symptoms before they reach 30 years of age, and the incidence rate within 5 years of graduation is high 5,9,11,12,15) . The suggested reason is that new physical therapists lack professional experience, knowledge, and techniques, and that they are rotationally dispatched to different places, thereby running a higher risk of injury 1,16) . More spinal symptoms related to WRMD have been found in female than in male therapists 9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation process began with a literature review of published studies that identified ergonomic risk factors associated with the primary tasks performed by physical therapists [9,10,11,13,15,16,28,29,30,31,32,33,34,35,36]. The identification of specific risk factors supported the development and adaptation of the questionnaire items.…”
Section: Adaptation Process Of the Jfq For Physical Therapistsmentioning
confidence: 99%
“…Previous researchers used questionnaires developed by others without first following international guidelines for evaluating the psychometric qualities of the instrument [10,15,27,28].…”
Section: Introductionmentioning
confidence: 99%